Molecular Imaging and Oral Cancer Diagnosis and Therapy. Issue 10 (23rd May 2017) - Keshavarzi, Maryam; Darijani, Mansoreh; Momeni, Fatemeh; Moradi, Pouya; Ebrahimnejad, Hamed; Masoudifar, Aria; Mirzaei, Hamed
ABSTRACT: Oral cancer is known as one of relatively common type of cancer worldwide. Despite the easy access of the oral cavity to examination, oral tumors are diagnosed in more advanced stages of the disease. Imaging techniques have been recently emerged as non‐invasive approaches to detect molecular and cellular changes in living cells and organisms. These techniques such as computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET) could help physicians to screen patients with oral tumors particularly oral squamous cell carcinoma (OSCC) in early stage of the disease. In this review, we discuss that early detection and diagnosis of oral tumors through using more robust and precise imaging techniques and a variety of cellular/molecular biomarkers not only could lead to more effective and less aggressive form of treatment for the disease but also could improve survival rates and lower treatment costs. J. Cell. Biochem. 118: 3055–3060, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Imaging techniques have been recently emerged as non‐invasive approaches to detect molecular and cellular changes in living cells and organisms. These techniques such as computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET) could help physicians to screen patients with oral tumors particularly oral squamous cell carcinoma (OSCC) in early stage of the disease.